Fibrous Bundles in Biomorph Systems: Surface‐Specific Growth and Interaction with Microposts. Issue 4 (11th February 2021) - Knoll, Pamela; D'Silva, Denvert S.; Adeoye, Damilola I.; Roper, Michael G.; Steinbock, Oliver
Abstract: Biomorphs are polycrystalline assemblies that form when barium, silicate, and carbonate ions react in basic solutions. Their micrometer‐scale morphologies include leaf‐like sheets, helices, and cones, while their nanoscale architecture is based on co‐aligned witherite nanorods. We report a biomorph shape that resembles hair strands that smoothly curl into spirals or twisting fiber ribbons. They can thicken through continuous fractal‐like branching or abrupt events in which fibers split simultaneously. Raman and energy dispersive X‐ray spectroscopy as well as optical polarization microscopy reveal that their composition is very similar to classical biomorphs. They are most abundant in the absence of glass substrates and at high pH values. However, if a glass surface is covered by a thin SU‐8 resin layer, their growth is observed and photolithographically produced SU‐8 posts serve as nucleation sites. The hair‐like structures can detach resin posts from the glass surface and reposition them due to continued growth at the hair‐resin interface. Collisions of growing biomorph sheets with SU‐8 posts result in overgrowth or a sheet‐to‐hair transition. Abstract : Chemistry's Fragile Harmonies : Inorganic microshapes, known as biomorphs, test our intuition of the morphological differences between living and abiotic shapes. These sheets, funnels, and helices are similar to biominerals and consist of co‐aligned nanocrystals, but simply require solutions containing barium and silicate to react with CO2 . Herein we describe a biomorph type that resembles hair strands and report its interaction with the resin SU‐8.